2002
DOI: 10.1242/jcs.00051
|View full text |Cite
|
Sign up to set email alerts
|

Epithelial monolayer wounding stimulates binding of USF-1 to an E-box motif in the plasminogen activator inhibitor type 1 gene

Abstract: Several proteases and their co-expressed inhibitors modulate the interdependent processes of cell migration and matrix proteolysis during wound repair. Transcription of the gene encoding plasminogen activator inhibitor type 1 (PAI-1), a serine protease inhibitor important in the control of barrier proteolysis and cell-to-matrix adhesion, is spatially-temporally regulated following epithelial denudation injury in vitro as well as in vivo. Using a well-defined culture model of acute epidermal wounding and reepit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
69
0

Year Published

2003
2003
2010
2010

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 47 publications
(69 citation statements)
references
References 75 publications
0
69
0
Order By: Relevance
“…These data provide the basis for a putative role of USF in regulating genes during adipocyte differentiation. The binding of USF-2 was demonstrated to inhibit PAI-1 expression in hepatocytes (Samoylenko et al 2001) whereas USF-1 increased PAI-1 transcription in epithelial cells (Providence et al 2002). We were able to demonstrate by competition experiments, and by the appearance of specific supershift bands in EMSA, that both USF-1 and USF-2 from adipocytic nuclear extracts can bind specifically to the PAI-1 promoter site.…”
Section: Discussionmentioning
confidence: 71%
“…These data provide the basis for a putative role of USF in regulating genes during adipocyte differentiation. The binding of USF-2 was demonstrated to inhibit PAI-1 expression in hepatocytes (Samoylenko et al 2001) whereas USF-1 increased PAI-1 transcription in epithelial cells (Providence et al 2002). We were able to demonstrate by competition experiments, and by the appearance of specific supershift bands in EMSA, that both USF-1 and USF-2 from adipocytic nuclear extracts can bind specifically to the PAI-1 promoter site.…”
Section: Discussionmentioning
confidence: 71%
“…Perhaps as importantly, PAI-1 not only stimulated keratinocyte adhesion and wound-initiated planar migration but also rescued keratinocytes from plasminogen-induced substrate detachment/anoikis. These effects may reflect the fact that PAI-1 accumulates specifically in the cellular undersurface region where it is wellpositioned to modulate integrin-ECM or uPA/uPAR-ECM interactions as well as stromal remodeling [2,3,6,[8][9][10]14,15,20,24,29,37,42]. Activation of the PAI-1 gene early after monolayer wounding and its prominence in the injury repair transcriptome are consistent with the present data suggesting a dual function for PAI-1 (i.e., as a keratinocyte survival factor and regulator of epithelial migration) in the cutaneous injury response program.…”
Section: Discussionmentioning
confidence: 99%
“…uPAR-associated uPA/PAI-1 complexes, moreover, are endocytosed by LRP family members potentially altering LRP and/or uPAR signaling events important in migratory decisions [6,7,9]. Collectively, PAI-1 may function within the global program of the tissue repair response to coordinate cycles of cell-to-substrate adhesion/detachment [7,8,10,24,27,29]. The association between the activated phenotype and targeted accumulation of PAI-1 in close proximity to newly formed focal adhesions [20] is consistent with this function.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that in relatives of FCHL patients there is an increased risk for CVD mortality, indicating that the predetermined genetic factors in these individuals may effect the disease progression independently of risk factors. 42 However, USF1 is biologically highly relevant, because it encodes a ubiquitously expressed transcriptional regulator of several genes, such as apo E, 43 CRP, 44 plasminogen activator inhibitor-1 45 and osteopontin, 46 which are functionally important for lipid accumulation, 47 inflammation, and thrombosis. All these proteins have been recovered directly from atherosclerotic plaques of artery wall, [48][49][50][51] and all of them have also been connected to the development of early atherosclerosis.…”
Section: Discussionmentioning
confidence: 99%